1983
DOI: 10.1111/j.1476-5381.1983.tb09397.x
|View full text |Cite
|
Sign up to set email alerts
|

The binding of [3H]‐diazepam to guinea‐pig ileal longitudinal muscle and the in vitro inhibition of contraction by benzodiazepines

Abstract: 1The longitudinal muscle-myenteric plexus strip preparation of the guinea-pig ileum was used to study the binding of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…However, diazepam does not affect the contractions induced by acetylcholine, 5-HT, histamine and electrical stimulation. Contrary to these results, Hullihan et al [17] found that diazepam produced a dose-dependent decrease in the electrically induced contractions of a longitudinal ileal muscle strip and antagonized the contractions induced by K + , Ca 2+ , histamine and carbachol. Another benzodiazepine, tetrazepam, produced concentration-dependent and complete relaxation of muscle contractions induced by KCl (80 mM) in the guinea pig ileum, and this relaxant action was not antagonized by pretreatment with hexamethonium (0.1 mM), an antagonist for nicotinic receptors, atropine (1 M), an antagonist for muscarinic receptors, or PK 11195 (1 M) antagonist for peripheral-type benzodiazepine receptors [34].…”
Section: Discussionmentioning
confidence: 57%
“…However, diazepam does not affect the contractions induced by acetylcholine, 5-HT, histamine and electrical stimulation. Contrary to these results, Hullihan et al [17] found that diazepam produced a dose-dependent decrease in the electrically induced contractions of a longitudinal ileal muscle strip and antagonized the contractions induced by K + , Ca 2+ , histamine and carbachol. Another benzodiazepine, tetrazepam, produced concentration-dependent and complete relaxation of muscle contractions induced by KCl (80 mM) in the guinea pig ileum, and this relaxant action was not antagonized by pretreatment with hexamethonium (0.1 mM), an antagonist for nicotinic receptors, atropine (1 M), an antagonist for muscarinic receptors, or PK 11195 (1 M) antagonist for peripheral-type benzodiazepine receptors [34].…”
Section: Discussionmentioning
confidence: 57%
“…The physiological significance of the non-neuronal benzodiazepine binding site is as yet unknown despite the presence of a high density of such sites in a wide variety of tissues (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Recently, however, several pharmacological effects have been ascribed to agents acting at these sites, and a common mechanism of action, that of calcium antagonism, has been suggested by these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines also bind to membranes from a variety of other tissues including kidney (5,6), heart (6, 7), lung (5,6), liver (5,6), mast cells (6), platelets (8), intestinal smooth muscle (9), several cell lines (10,11), and central nervous system non-neuronal elements (12)(13)(14)(15). The sites on these latter cell types represent a population of binding sites pharmacologically distinct from the neuronal type because of the different structural requirements for their respective ligands (unpublished data).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca yabani memelilerin hareketsiz bırakılarak yakalanmaları ile bunların sağaltım ve zoolojik işlemlerini kolaylaştır-mada, hareketsiz kılıcı madde olarak yararlanılmaktadır (1,3,4,9). Bundan başka insanlarda geniş ölçekli kas gevşetici, antikonvülzan, anksiyolitik ve hipnotik amaç-larla uygulandığı da bilinmektedir (7,8,19).…”
Section: Introductionunclassified